2022
DOI: 10.3897/mbmg.6.78181
|View full text |Cite
|
Sign up to set email alerts
|

Annual dynamics of eukaryotic and bacterial communities revealed by 18S and 16S rRNA metabarcoding in the coastal ecosystem of Sagami Bay, Japan

Abstract: Sagami Bay, Japan is influenced by both the warm Kuroshio Current and the cold Oyashio Current and rich nutrients are supplied from multiple river sources and the deep-sea, forming a dynamic ecosystem. The aim of the present study was to investigate eukaryotic and bacterial communities in the coastal waters of Sagami Bay, using 16S rRNA and 18S rRNA sequencing and to assess the seasonal and vertical dynamics in relation to physicochemical and biological conditions. Eukaryotic and bacterial communities showed s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 96 publications
(108 reference statements)
0
2
0
Order By: Relevance
“…On 19 April 2019, 19′-HF concentration was at the highest value recorded during the survey period (Fig. 9), and on the same day, within haptophytes, Prymnesiales abundance also comprised the highest number of genetic reads between 0-10 m depth followed by Phaeocystales and Coccolithales (Sogawa et al 2022). Although it should be noted in taxonomic discussions that G. oceanica belongs to the order Isochrysidales, these results suggest that haptophyte occurrence, including coccolithophores, may be more prevalent than previously assumed in Sagami Bay.…”
Section: The Frequency Of Coccolithophore Appearance and Biodiversitymentioning
confidence: 88%
See 1 more Smart Citation
“…On 19 April 2019, 19′-HF concentration was at the highest value recorded during the survey period (Fig. 9), and on the same day, within haptophytes, Prymnesiales abundance also comprised the highest number of genetic reads between 0-10 m depth followed by Phaeocystales and Coccolithales (Sogawa et al 2022). Although it should be noted in taxonomic discussions that G. oceanica belongs to the order Isochrysidales, these results suggest that haptophyte occurrence, including coccolithophores, may be more prevalent than previously assumed in Sagami Bay.…”
Section: The Frequency Of Coccolithophore Appearance and Biodiversitymentioning
confidence: 88%
“…However, it should be noted that 19′-HF alone cannot confidently discriminate only coccolithophores since coccolithophores are only one kind of haptophyte. A recent study of prokaryotic and eukaryotic community structure using genetic analysis reported that coccolithophores were detected in October 2018, April, May, July, and August 2019, and February 2020 between 0-10 m depth at St. M, appearing six times out of 23 samplings (Sogawa et al 2022) burth, 1984burth, (Sogawa et al 2022). On 19 April 2019, 19′-HF concentration was at the highest value recorded during the survey period (Fig.…”
Section: The Frequency Of Coccolithophore Appearance and Biodiversitymentioning
confidence: 99%